MODEL KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY (CSR) BANK INDONESIA - Puji Lestari (Jurnal Ilmu Komunikasi, 2009)
The purpose of this research was found a model of communication between companies, Bank Indonesia (BI) and Small Medium Entreprises (SME) in Bantul, and communities. This research used subjective approach by qualitative data. The data collection was conducted using interview. Subjects of this research included occured SME who suffered the earthquake in Manding, Bantul Regency. Another subject was Corporate Social Responsibility (CSR) team from BI Yogyakarta. The data analysis was conducted qualitatively. This research found synergic communication model among Bank Indonesia, government, and society Through CSR Program. CSR Program of BI had fulfilled the systematic of CSR program that suggested by Ambadar, i.e. by planning the implementation and evaluation. The communication held between the company, government, and constructed partner, i.e. SME in Manding industrial centre had been intensive, through the official meeting, reviewing and informally via telephone. CSR program conducted included successful in outsourcing the SME post-earthquake in Manding, Bantul Regency. It seem by the existence of human resources of which had followed English course and computer, physical development by shape of parking lots, ATM, the meeting hall, gates as identity as letter handicraft centre of Manding, and the ballyhoo concerning on Manding, there are plenty of crowd shops visited by both domestic or foreign consumers.